Reactive Oxygen Species, Redox Signaling and Neuroinflammation in Alzheimer's Disease: The NF-κB Connection - Kaur, Upinder; Banerjee, Priyanjalee; Bir, Aritri; Sinha, Maitrayee; Biswas, Atanu; Chakrabarti, Sasanka (Current Topics in Medicinal Chemistry, 2015)
Oxidative stress and inflammatory response are important elements of Alzheimer's disease (AD) pathogenesis, but the role of redox signaling cascade and its cross-talk with inflammatory mediators have not been elucidated in details in this disorder. The review summarizes the facts about redox-signaling cascade in the cells operating through an array of kinases, phosphatases and transcription factors and their downstream components. The biology of NF-κB and its activation by reactive oxygen species (ROS) and proinflammatory cytokines in the pathogenesis of AD have been specially highlighted citing evidence both from post-mortem studies in AD brain and experimental research in animal or cell-based models of AD. The possibility of identifying new disease-modifying drugs for AD targeting NF-κBsignaling cascade has been discussed in the end.
Keywords: Cytokines